El control interno contable de cuentas por cobrar y su aporte a la razonabilidad en los estados financieros - Córdova Sotomayor, Karla Alexandra (2015)
This project's main objective is to dissect the meanings of what is internal control of accounts receivable and as affects the fairness of the financial statements. For its development has been used several investigations, these are framed in the analysis of literature sources, scientific papers, articles, books and frequent consultations through the internet, it could also be done the preparation of a manual of internal control that have helped develop a more explicit context regarding internal control for accounts receivable refers. It should be noted that internal control of accounts receivable aims to properly implement accounting controls by monitoring and timely structure that allows the organization to reach a level of development more reliable.